2020
DOI: 10.1021/acs.analchem.9b05252
|View full text |Cite
|
Sign up to set email alerts
|

Automated Determination of Dissolved Reactive Phosphorus at Nanomolar to Micromolar Levels in Natural Waters Using a Portable Flow Analyzer

Abstract: Automated in-field methods for measuring dissolved reactive phosphorus (DRP) over a large concentration range are in high demand for the purpose of better understanding the biogeochemistry of phosphorus in the river-estuary-coast continuum to the open ocean. Here, an automated portable and robust analyzer was described for the determination of nanomolar to micromolar levels of DRP in natural waters. The quantification of DRP was based on classic phosphomolybdenum blue (PMB) chemistry. All the components of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The parameters related to chemical reaction and flow analysis have been comprehensively evaluated and optimized in previous publications using i SEA-I. With the updated version ( i SEA-II), these optimized values were checked and reconfirmed to be suitable for the new hardware. Table summarizes the analytical figures of the merit of the i SEA-II system after minor optimization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The parameters related to chemical reaction and flow analysis have been comprehensively evaluated and optimized in previous publications using i SEA-I. With the updated version ( i SEA-II), these optimized values were checked and reconfirmed to be suitable for the new hardware. Table summarizes the analytical figures of the merit of the i SEA-II system after minor optimization.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information on chemical preparation can be found in the Supporting Information and previous papers. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28] LabVIEW VIs were also utilized for the precise control and monitoring of hardware components of automated SIA systems. [29][30][31] However, to the best of our knowledge, the open code LabVIEW software for zone penetration studies was not yet reported. Our main objective was to develop LabVIEW VI that would not only provide the user with the most fundamental peak-related parameters but it would also support zone penetration studies in flow-based analytical systems, by evaluating peak overlapping areas.…”
Section: Accepted Manuscriptmentioning
confidence: 99%